2013
DOI: 10.11646/zootaxa.3635.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity within the Redeye Bass, Micropterus coosae (Perciformes: Centrarchidae) species group, with descriptions of four new species

Abstract: The Redeye Bass, Micropterus coosae, was described from the Mobile River basin, Chattahoochee, and Savannah rivers in Alabama and Georgia, USA, by Hubbs and Bailey (1940). At that time the authors recognized significant variation in the Black Warrior River population, and noted that with further study this form may be recognized as a separate taxon. An examination of variation in morphology and mitochondrial DNA supported this observation, and highlighted additional species-level variation, resulting in descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 20 publications
1
50
0
Order By: Relevance
“…); and a western group consisting of Redeye Bass, Tallapoosa Bass M. tallapoosae , Cahaba Bass M. cahabae , and Warrior Bass M. warriorensis , which share a common ancestor with Alabama Bass (Baker et al. ). Using morphological evidence, Baker et al.…”
Section: Diversity and Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…); and a western group consisting of Redeye Bass, Tallapoosa Bass M. tallapoosae , Cahaba Bass M. cahabae , and Warrior Bass M. warriorensis , which share a common ancestor with Alabama Bass (Baker et al. ). Using morphological evidence, Baker et al.…”
Section: Diversity and Distributionmentioning
confidence: 99%
“…Using morphological evidence, Baker et al. () elevated Chattahoochee Bass and the three novel members (Tallapoosa, Cahaba, and Warrior Bass) of the western group. However, upon post‐hoc examination of the mitochondrial ND 2 sequences accessioned by these authors, members of the western species group are revealed to be unresolved with respect to Alabama Bass (Freeman et al.…”
Section: Diversity and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most tips were assigned a value of one, although our tree contained 32 of the 38 currently known centrarchid species. We collapsed Micropterus coosae into a total of five species (Baker et al 2013), and both Micropterus punctulatus and Lepomis megalotis into two species (Baker et al 2008;Warren 2009). MEDUSA starts by fitting a birth-death, two-parameter model to the tree.…”
Section: Lineage Diversificationmentioning
confidence: 99%
“…The genus Micropterus Lacépède 1802 (family Centrarchidae) contains 13 North American species of black basses (Baker, C.S. et al ., ; Baker, W. H. et al ., ), which are top carnivores and popular sport fishes (Bagley et al ., ). The wide‐ranging smallmouth bass M .…”
Section: Introductionmentioning
confidence: 99%